The Effect of Belief Elicitation Game Play - Timo Hoffmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The assumptions that subjects hold beliefs and that the chosen actions are not altered by a proper elicitation of these beliefs are widely used in economics. In this paper I experimentally test whether the second assumption is correct. Especially controlling for different game properties, I nd that in dominance solvable two-player normal-form games belief elicitation results in a signi cant increase of equilibrium play. Therefore the elicitation of beliefs can affect the choices made by subjects and lead to more equilibrium actions being chosen. Surprisingly one major reason for this effect is the decreased play of own dominated actions. The results indicate that belief elicitation induces subjects to think harder about the presented decision situation, which results in a better understanding of the given situation and consequently in a modi cation of their beliefs. Therefore, in certain decision situations, belief elicitation affects the decisions made by subjects.
Keywords: C72; C91; D83; 330